The The Influence of Leadership Style, Workload, and Compensation Variables on Employee Turnover Intention - Uswatun Hasanah; Suwignyo Widagdo; Diana Dwi Astuti (Trescode Green Organization, 2025)
Study This motivated by the height level turnover intention at PT. Hoki Marine Corp, especially in the maintenance division, which has an impact negative to effectiveness and sustainability operational company. Research objectives is analyze influence style leadership, burden work and compensation to turnover intention employees, good in a way partial and simultaneous. Research method use approach quantitative with technique survey through distribution questionnaire to 133 respondents. Data analysis was carried out use multiple linear regression For test connection between variables. Research results show that in a way partial style leadership influential negative and significant to turnover intention, burden Work influential positive and significant, whereas compensation influential negative and significant. In terms of simultaneous, third variables the influential significant to turnover intention, findings this indicates that improvement quality leadership, management burden proportional work, as well as giving fair and appropriate compensation performance can lower intention employee to go out from company. Therefore that, the company need give attention to the three aspect the as part from management strategy source of power sustainable human beings.